Principally Quasi injective system over monoid - Amer, Shaymaa (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this work , principally quasi injective system has been introduced and studied , which is a generalization of quasi injective system . We obtain a characterizations of PQ-injective systems , conditions on which, subsystems inherit the property of PQ-injectivity , and conditions have been considered to versus PQ-injective system. Finally , the relationship between maximal reversible subsystem of system and maximal left ideal of the endomorphism monoid of the system has been studied .